Ergonomics and Regulation: The Case of Job Rotation in a Brazilian Slaughterhouse - de Anchieta Messias, Iracimara; Nascimento, Adelaide (Springer Nature, 2019)
In April 2013, Regulatory Standard 36 was published in Brazil, concerning health and safety at work in slaughtering and meat processing companies, aiming to establish, among other things, standards for the implementation of job rotation. This industry has expanded in Brazil, which is currently the world’s largest exporter of beef. This work presents partial data from a survey carried out in a cattle slaughterhouse located in the state of São Paulo, Brazil. The purpose of this communication is to present the acceptance of the slaughterworkers regarding the rotation of posts imposed by the legislation, as well as to identify the determinants of the work. According to the data obtained, the slaughtering sector is composed of 88 workers, of which 91% are male and 47% aged 40 to 54 years. The most common causes of absenteeism in last two years were inguinal and abdominal hernias. The most significant determinants of labor are: product variation (cattle differences), cadence and irregular work rate, and physical and psychological demands. Knives, the main work tools, require time to be cleaned and sharpened. Concerning acceptance of the rotation, 30% of the workers are in favor, as they will learn new activities, and 70% are contrary as they believe they will be more exposed to work accidents in activities for which they do not have specific skills. It is concluded that detailed analysis of the posts, with the effective participation of the workers, are the main steps to comply with current legislation and preserve health at work and reduce the number of accidents and occupational diseases.
Keywords: Ergonomics; Job rotation; Slaughterhouse